Barriers to Adoption of Products and Technologies that Aid Risk Management in Developing Countries - Brown, Julia K.; Zelenska, Tetyana V.; Mobarak, Mushfiq A. (World Bank, Washington, DC, 2013)
Risk is an important facet of life in developing countries; households are subject to both aggregate risks as well as idiosyncratic risks. In an attempt to broaden the scope of the discussion concerning the puzzlingly low demand for other types of income-generating and (ex-ante) risk-mitigating technologies, products and behaviors, this paper highlights the most important aspects of human decision-making and constraints facing poor households that keep the market penetration of welfare improving products low. The latest state-of-the art literature on the demand for insurance, seasonal migration and cell phone services relevant to risk management is reviewed in an effort to understand reasons why adoption of risk management tools are being held back in hopes of further identifying knowledge gaps and securing a direction for the future.